Хімічне знання у контексті розвитку цивілізації - Коломак, Олеся Ігорівна (НТУ "ХПІ", 2018)
Віссю розвитку людської цивілізації була і є проблема виживання людського суспільства. Успіхи людини у вирішенні великих і малих проблем виживання в значній мірі були досягнуті завдяки розвитку хімії, становленню різних хімічних технологій. Від стану і розвитку хімії залежать успіхи багатьох галузей людської діяльності. Сучасний розвиток хімії, як і розвиток інших наук – інтеграційний процес. Саме на цій основі виникають нові галузі знання. Найсерйозніші відкриття нині здійснюються саме на «перетині» наук, їх предметному переплетенні.

The axis of the development of human civilization was and is the problem of the survival of human society. The success of man in solving large and small survival problems was largely achieved through the development of chemistry, the formation of various chemical technologies. The state and development of chemistry depends on the successes of many branches of human activity. Modern development of chemistry, as well as the development of other sciences - the integration process. It is on this basis that there are new branches of knowledge. The most serious discoveries are now made on the "intersection" of sciences, their subject-matter interweaving.
Chemical knowledge in the context of development of civilization
Keywords: хімія; інтеграція; НБІК-технології; chemistry; integration; NBIK-technologies